Tackling climate change at the city level: insights from Lighthouse Cities' climate mitigation efforts - Biresselioglu, Mehmet Efe; Savas, Zehra Funda; Demir, Muhittin Hakan; Kentmen-Cin, Cigdem (Frontiers in Psychology, 2024)
Introduction The link between lifestyles and Greenhouse Gas (GHG) emissions has prioritized climate mitigation strategies of cities worldwide. As cities have increasingly generated GHG emissions by their industrial and transportation activities, their role in climate mitigation has gained prominence. Cities' climate mitigation policies to reduce the GHG intensity of their residents' daily lives are one of their significant efforts to tackle climate change. Lighthouse Cities (LCs), in particular, have emerged as remarkable actors in promoting lifestyle changes for their residents. Methods This study examines climate mitigation strategies of LCs of Climate CAMPAIGNers project, including Baku, Vilnius, Lahti, Izmir, Trujillo, Athens, Linz, Milan, Cape Town, Dublin, and Skopelos, addressing lifestyle changes by conducting an expert survey in 11 LCs involving 89 respondents. The findings of the expert survey are comparatively analyzed across 11 LCs. Results The results show that experts form Lighthouse Cities identify increasing awareness and information provision as a significant component of climate mitigation policies. Concerning lifestyle changes, strategies toward energy efficiency and sustainable mobility are highlighted as the primary areas to be prioritized. Discussion This study enhances the understanding of cities' capacity to reduce their residents' GHG emissions. The findings can be utilized to identify and tailor policies for supporting the Lighthouse Cities in their climate change mitigation efforts and provide pointers for selecting the lifestyle changes that can be promoted and prioritized in Lighthouse Cities.